Parabacteroides as a promising target for disease intervention: current stage and pending issues - Jing Liu; Hui Qiu; Jiamin Zhao; Nan Shao; Chao Chen; Zhixu He; Xu Zhao; Juanjuan Zhao; Ya Zhou; Lin Xu (npj Biofilms and Microbiomes)
Abstract Parabacteroides, a promising candidate for the next generation of probiotics, plays a significant role in various diseases. In this review, we provide a comprehensive examination of the biological properties of Parabacteroides, summarize its effects on host health and potential associations with diseases, and discuss unresolved scientific questions regarding this genus. Our aim is to offer novel insights for the development of targeted gut microbiota interventions and their translational applications.